2021
DOI: 10.23887/jippg.v4i3.39810
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kinerja Guru pada Masa Pandemi Dengan Sistem Daring

Abstract: Masa pandemi yang terjadi saat ini memberikan pengaruh terhadap berbagai bidang kehidupan termasuk bidang pendidikan. Sebagai salah satu upaya pemerintah dalam menanggulangi pandemi dan usaha untuk tetap melaksanakan pembelajaran maka sistem pembelajaran normal dialihkan menjadi pembelajaran daring. Adanya pandemi menyebabkan kinerja guru menurin. Penelitian ini bertujuan untuk menganalisis peningkatan kinerja guru di masa pandemi dengan sistem daring. Jenis penelitaian ini menggunakan metode penelitian litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The teachers are trying to independently find out the learning media they can use to help and make it easier for them to carry out teaching and learning activities during a pandemic like this. Ayunda et al (2021) revealed that teachers must seek and use new and varied strategies for students so that learning can run effectively. These varied strategies make students more enthusiastic in the learning process to make it easier to understand the learning material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The teachers are trying to independently find out the learning media they can use to help and make it easier for them to carry out teaching and learning activities during a pandemic like this. Ayunda et al (2021) revealed that teachers must seek and use new and varied strategies for students so that learning can run effectively. These varied strategies make students more enthusiastic in the learning process to make it easier to understand the learning material.…”
Section: Discussionmentioning
confidence: 99%
“…Even if they have to buy them, the price is relatively high, so many teachers and parents of students object. Furthermore, even if all these technological devices are available, there are still teachers who still do not know about the learning platform Ayunda et al, (2021); not all teachers understand how to operate the platform for online learning activities to take place because online learning requires various platforms that previously were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few examples as the decline in teacher performance during the pandemic due to various obstacles, such as difficulties in delivering learning materials directly, teaching orientation is only on achieving material targets and pursuing high score targets on tests, thus causing the quality of the learning process to be neglected and causing the quality of the learning process to be low and less meaningful. for students (Ayunda, 2021;Alifia and Pramana, 2021).…”
Section: B Education Systematics In Indonesia Before the Covid-19 Pan...mentioning
confidence: 97%
“…Pembelajaran secara daring/online adalah salah satu upaya pemerintah dimasa pandemic Covid-19 agar proses pembelajaran tetap terlaksana (Ririn Humaera, 2020). Pembelajaran daring menggunakan media digital dalam pelaksanaanya dan dilakukan dari jarrah jauh (Ayunda et al, 2021). Tenaga pendidik diharuskan bisa beradaptasi mengatasi situasi pendidikan saat ini agar kualitas hasil pembelajaran tetap terjaga dan tidak menurun.…”
Section: Pendahuluanunclassified